Is there a role for fetal ductus venosus and hepatic artery Doppler in screening for fetal aneuploidy in the first trimester?. (6th October 2014) - Togrul, Cihan; Ozaksit, Gulnur M.; Seckin, Kerem D.; Baser, Eralp; Karsli, Mehmet F.; Gungor, Tayfun
Abstract: Objective : The aim of the present study was to evaluate the utility of ductus venosus (DV) and hepatic artery (HA) doppler in pregnant women who have high risk for aneuploidy in first trimester combined screening. Methods : This prospective study was performed between February 2011 and February-2012, at a tertiary referral hospital. Singleton pregnancies with high risk for aneuploidy in combined screening test and normal nuchal translucency (NT) measurements were included in the study group. Measurements of DV Pulsatility Index of Veins (PIV) and HA Pulsatility Index (PI) were compared between the study group and controls. Results : Within the study period, 104 women with singleton pregnancies were evaluated for DV and HA measurements and among these, 64 women met the inclusion criteria. A control group that comprised 40 women with similar gestational age, normal NT measurements and low-risk in first trimester combined tests was generated. DV-PIV measurements were significantly higher ( p  = 0.03), whereas HA-PI measurements were similar ( p  > 0.05) in women who had high-risk for aneuploidy in first trimester combined test. Conclusion : We concluded that the addition of DV-PIV and HA-PI measurements to the first trimester combined screening might increase the accuracy for Down syndrome detection.